Efeito da adição de cama de galinheiro ao capim-elefante ’Napier’ (Pennisetum purpureum, Schum) sobre as características de fermentação da silagem - Lavezzo , Wagner; Campos, Joaquim (Revista Ceres, 2025)
Effects of the addition of chicken litter to Napier grass (Pennisetum purpureum Schum.) in preparation of silage were studied.